2007
DOI: 10.1021/ac070832g
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Infrared Chemical Sensors Utilizing Plasma-Deposited Fluorocarbon Membranes

Abstract: In this study, plasma-polymerized films are evaluated as enrichment membranes deposited at the surface of mid-infrared transparent waveguides for liquid-phase chemical sensing utilizing evanescent field absorption spectroscopy. Fluorocarbon films were deposited onto zinc selenide (ZnSe) waveguides from plasma-polymerized pentafluoroethane (CF(3)CHF(2)) vapor. Excellent optical transmission of ZnSe waveguides after plasma deposition confirms compatibility of the infrared transparent substrate with this low-temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…The incorporation of such films into chemical sensors has been heavily researched since the late 1980s [68, 69]. EPLs have been demonstrated as efficient and highly sensitive coatings for diverse evanescent waveguide-based optical monitoring systems [7076]. On exposure to specific analytes, the polymeric coatings will change their internal structure reversibly or irreversibly at the nano-level by swelling with an analyte.…”
Section: Sensor Functionalization For Enhanced Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of such films into chemical sensors has been heavily researched since the late 1980s [68, 69]. EPLs have been demonstrated as efficient and highly sensitive coatings for diverse evanescent waveguide-based optical monitoring systems [7076]. On exposure to specific analytes, the polymeric coatings will change their internal structure reversibly or irreversibly at the nano-level by swelling with an analyte.…”
Section: Sensor Functionalization For Enhanced Specificitymentioning
confidence: 99%
“…Many different polymer materials have been compared to determine the most effective enrichment layer for specific analytes [70, 77, 78]. The optical properties of polymer film swelling versus film thickness have also been studied [79].…”
Section: Sensor Functionalization For Enhanced Specificitymentioning
confidence: 99%
“…Fluorocarbon films deposited onto IREs have been successfully developed for trace organic contaminant determination in water. 46 Tetrachloroethylene was selected as model analyte providing limits of detection below 300 nL L À1 .…”
Section: Preconcentration Strategiesmentioning
confidence: 99%
“…8 It was demonstrated that the sensitivity of this technique can be vastly increased using selective enrichment layers coated on ATR crystals that cover the volume probed by the evanescent field. [9][10][11] Until now, they have been primarily employed for enriching apolar substances into hydrophobic coatings. In this context, we have successfully shown that organically functionalized mesoporous silica films can also be employed.…”
Section: Introductionmentioning
confidence: 99%